Design of Second Order Sliding Mode for Glucose Regulation Systems with Disturbance - Jaleel Humaidi, Amjad; Hasan, Sami; Abdulhussein Al-Jodah, Ammar (International Journal of Engineering and Technology, 2018)
In this work, Design of second order sliding mode control has been developed to control the diabetic glucose concentration level under disturbing meal has been controlled using three sliding mode controllers. A comparative study of three sliding mode controllers is made in terms of robustness characteristics due to meal feeding. The first is the classical sliding mode controller, the second is integral sliding mode controller and the third is the second order sliding mode controller. Due to their characteristic features of disturbance rejection, all the three sliding mode controllers are presented here for comparison. The Bergman minimal mathematical model is used to describe the dynamic behavior of blood glucose concentration due to insulin regulator injection. Simulations, based on MATLAB/Simulink, were performed to verify the performance of each controller. It has been shown that integral and second order sliding mode controllers are the best of all in terms of disturbance rejection capability.Â